THE DIFFERENCE IN EMOTIONAL INTELLIGENCE BETWEEN THE UNDERGRADUATE AND POSTGRADUATE ENGLISH EDUCATION STUDENTS AT THE UNIVERSITY OF BENGKULU - Bambang Suwarno; Safnil safnil; Ira Maisarah (Edu-Ling: Journal of English Education and Linguistics, 2020)
The study aims to explore whether there is any difference in emotional intelligence (EQ) between the undergraduate and postgraduate students at the English education programs of the University of Bengkulu (Unib). The research design was ex-post facto. The sample included a number of English program students at both programs. The instrument was an emotional intelligence questionnaire. In data analysis, non-parametric tests were used. The result showed there was a significant difference in emotional intelligence between both groups. Futher study and teaching are recommended to improve the EQ of the undergraduate students.